2012
DOI: 10.1111/j.1741-2358.2012.00666.x
|View full text |Cite
|
Sign up to set email alerts
|

Chewing number is related to incremental increases in body weight from 20 years of age in Japanese middle‐aged adults

Abstract: Although this study was limited because it did not consider all risk factors, categorical chewing number was related independently to body weight increments of more than 10 kg from 20 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 18 publications
0
26
0
2
Order By: Relevance
“…Several studies have reported that eating speed has a positive relationship with obesity in almost all age groups and populations [13,14,15,16,17,18]. This relationship may be explained by the following two aspects: i) Less mastication activates fewer histamine neurons in the brain, leading to delayed sense of stomach fullness and resulting in overeating.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that eating speed has a positive relationship with obesity in almost all age groups and populations [13,14,15,16,17,18]. This relationship may be explained by the following two aspects: i) Less mastication activates fewer histamine neurons in the brain, leading to delayed sense of stomach fullness and resulting in overeating.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that eating speed plays a role in obesity [13,14,15,16,17,18,19,20] and diabetes [21,22,23]; therefore, it is recommended that we chew well and eat slowly. A gradual elevation of blood glucose level is recommended in order to prevent overworking the pancreas which can result from continued and rapid insulin secretion [24].…”
Section: Introductionmentioning
confidence: 99%
“…Among the above studies, only the study by Kohyama et al (2003) considered the potential effect of body mass index (BMI) and reported that BMI was not significantly different between young and older adults in their study; other studies (Cecilio et al, 2010;Galo et al, 2006Galo et al, , 2007Kohyama et al, 2002;Kohyama & Mioche, 2004;Mioche et al, 2004b;Mishellany-Dutour et al, 2008) had not adjusted for BMI in their analysis. While accumulating data supporting the relationship between chewing behavior and energy hemostasis or body weight status have been published recently (Cassady et al, 2009;Fukuda et al, 2013;Hamada et al, 2014;Li et al, 2011;Smit et al, 2011;Zhu & Hollis, 2014aZhu et al, 2013Zhu et al, , 2014, it raises the possibility that differences in chewing behavior between young and older adults reported in previous studies (Cecilio et al, 2010;Galo et al, 2006Galo et al, , 2007Kohyama & Mioche, 2004;Kohyama et al, 2002;Mioche et al, 2004b;Mishellany-Dutour et al, 2008) may be confounded by body weight status. Therefore, studies that compare chewing behaviors between young and older adults that adjust for these confounding factors are needed; such studies are not only important for a better understanding of aging-related mastication problems, but also may provide additional information to explain for the reduced appetite in older adults, as previous studies reported that increased number of chewing cycles before swallowing results in reduced appetite (Zhu et al, 2013(Zhu et al, , 2014 and reduced food intake (Li et al, 2011;Smit et al, 2011).…”
Section: Introductionmentioning
confidence: 88%
“…Notably, various eating behaviors have recently been associated with obesity and/or other metabolic syndromes (Fukuda et al ., ; Muñoz‐Pareja, Guallar‐Castillón, Measa, López‐García‐García, & Rodríguez‐Artalejo, ; Nurkkala et al ., ; Otsuka et al ., ; Smit, Kemsley, Tapp, & Henry, ; Sonoki et al ., ; Spiegel, ; Zijlstra, de Wijk, Mars, Stafleu, & de Graaf, ). The number of chews for each mouthful of food is one example of an eating parameter that can affect health.…”
Section: Introductionmentioning
confidence: 99%